2013
DOI: 10.1002/da.22059
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety in Physical Activity Participation in Patients With Mental Illness: A Cross-Sectional Multicenter Study

Abstract: Our data indicate that patients with mental illness reported higher levels of SA in PA situations compared to healthy control subjects. Health professionals should consider SA when trying to improve outcome and adherence of patients with mental illness to PA interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…A potential hypothesis of the link between low PA and anxiety may be explained also by the social withdrawal theory which posits that not engaging in PA may lead to social solitude and withdrawal from interpersonal relationships, both of which have been linked to increased feelings of social anxiety and depression . On the other hand, it may be that those with anxiety are less inclined to engage in PA as a means of coping with their anxiety symptoms, as has been suggested in previous research amongst people with mental illness with social physique anxiety . We also did find a negative association with MCI in older people with depression.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A potential hypothesis of the link between low PA and anxiety may be explained also by the social withdrawal theory which posits that not engaging in PA may lead to social solitude and withdrawal from interpersonal relationships, both of which have been linked to increased feelings of social anxiety and depression . On the other hand, it may be that those with anxiety are less inclined to engage in PA as a means of coping with their anxiety symptoms, as has been suggested in previous research amongst people with mental illness with social physique anxiety . We also did find a negative association with MCI in older people with depression.…”
Section: Discussionsupporting
confidence: 76%
“…54 On the other hand, it may be that those with anxiety are less inclined to engage in PA as a means of coping with their anxiety symptoms, as has been suggested in previous research amongst people with mental illness with social physique anxiety. 55 We also did find a negative association with MCI in older people with depression. MCI is associated with impairments in executive functioning and can result in slow gait and an increased risk of falls in older people, which on its turn is associated with a fear to fall again and avoidance of PA, 56 in particular in those who are depressed.…”
Section: Resultssupporting
confidence: 55%
“…A recent meta-analysis suggests that high levels of stress and low mood along with lack of social support are leading barriers to exercising [109]. A cross- sectional study also suggests that social anxiety may contribute to sedentary behavior [110]. …”
Section: Ressing Potential Barriers To Exercise Treatment For Smentioning
confidence: 99%
“…Those studies have found some barriers to performing physical activities. These barriers are the adverse effects of the antipsychotic drugs, psychiatric symptoms, social anxiety, lack of motivation, and socioeconomic insufficiencies . However, the number of studies determining the perceptions and barriers toward a healthy eating status are limited in individuals with mental illness.…”
Section: Introductionmentioning
confidence: 99%